IL-10 partly mediates the ability of MSC-derived extracellular vesicles to attenuate myocardial damage in experimental metabolic renovascular hypertension - Jiang, Yamei; Hong, Siting; Zhu, Xiangyang; Zhang, Lei; Tang, Hui; Jordan, Kyra L.; Saadiq, Ishran M.; Huang, Weijun; Lerman, Amir; Eirin, Alfonso; Lerman, Lilach O. (Frontiers in Immunology, 2022)
Extracellular vesicles (EVs) obtain properties of immunomodulation and tissue repair from their parental mesenchymal stem cells (MSCs), and upon delivery may be associated with fewer adverse events. EVs derived from adipose-tissue MSCs restored kidney function by attenuating kidney inflammation in a swine model of metabolic syndrome (MetS) and renal artery stenosis via anti-inflammatory pathways. EVs also ameliorated myocardial injury in renovascular hypertension (RVH) secondary to inflammation in cardiorenal disease, but the mechanisms regulating this effect are unknown. We hypothesize that the anti-inflammatory cytokine interleukin (IL)-10 mediates the reparative effects of EVs on cardiovascular complications in a preclinical swine model with coexisting MetS and RVH. Twenty-three pigs established as Lean controls or RVH models were observed for 16 weeks. At 12 weeks RVH subgroups received an intrarenal delivery of 1011 either wildtype (WT) EVs or EVs after IL-10 knockdown (KD) (RVH+WT-EVs or RVH+IL-10-KD-EVs, respectively). Cardiac and renal function were studied in-vivo and myocardial tissue injury in-vitro 4 weeks later. RVH pigs showed myocardial inflammation, fibrosis, and left ventricular diastolic dysfunction. WT-EVs attenuated these impairments, increased capillary density, and decreased myocardial inflammation in-vivo. In-vitro, co-incubation with IL-10-containing WT-EVs decreased activated T-cells proliferation and endothelial cell inflammation and promoted their migration. Contrarily, these cardioprotective effects were largely blunted using IL-10-KD-EVs. Thus, the anti-inflammatory and pro-angiogenic effects of EVs in RVH may be partly attributed to their cargo of anti-inflammatory IL-10. Early intervention of IL-10-containing EVs may be helpful to prevent cardiovascular complications of MetS concurrent with RVH.